Penerapan Customer Relationship Management (CRM) Dalam Meningkatkan Kualitas Layanan Pada Toko Yayyshop - Rafiqa Mulia Indah Sari Sam; Seni Asria; A. Edeth Fuari Anatasya; Syahrul, Syahrul (Prosiding SISFOTEK, 2023)
Yayyshop shop is a business engaged in selling cosmetics and skincare. The yayyshop shop is located at Bumi Pratama Residance Jl. Tamangapa Raya No.3 Bangkala Village, Antang, Manggala District. Problems arise from online marketing because many customers complain about the services provided, such as slow responses, products not being available, slow complaint handling and less than optimal admin performance. The had a negative impact on the store, including reduced customer loyalty and increased cancellation of product orders. Yayyshop shops also don’t have a system to manage and store transaction data, customer data and sales reports, so the process is still manual and takes quite a long time. The purpose of this research is to build a system that can run its business processes and improve the quality of service to customers by implementing a business strategy, namely CRM (Customer Relationship Management). Customer Relationship Management is a comprehensive strategy for stores so that the life cycle of each customer can be used optimally. The result of implementing Customer Relationship Management (CRM) on the Yayyshop shop website are suitable for use, with an answer percentage of 80% of testers agreeing with the display of information on the website, 70% strongly agreeing with the ease of use of menus and features, 70% using this system is overall satisfactory.